High-fat diet induces apoptosis of hypothalamic neurons. - Juliana C Moraes (Public Library of Science (PLoS), 2009)
Consumption of dietary fats is amongst the most important environmental factors leading to obesity. In rodents, the consumption of fat-rich diets blunts leptin and insulin anorexigenic signaling in the hypothalamus by a mechanism dependent on the in situ activation of inflammation. Since inflammatory signal transduction can lead to the activation of apoptotic signaling pathways, we evaluated the effect of high-fat feeding on the induction of apoptosis of hypothalamic cells. Here, we show that consumption of dietary fats induce apoptosis of neurons and a reduction of synaptic inputs in the arcuate nucleus and lateral hypothalamus. This effect is dependent upon diet composition, and not on caloric intake, since pair-feeding is not sufficient to reduce the expression of apoptotic markers. The presence of an intact TLR4 receptor, protects cells from further apoptotic signals. In diet-induced inflammation of the hypothalamus, TLR4 exerts a dual function, on one side activating pro-inflammatory pathways that play a central role in the development of resistance to leptin and insulin, and on the other side restraining further damage by controlling the apoptotic activity.